Development and Validation of Chinese University Students’ Physical Activity Motivation Scale Under the Constraint of Physical Education Policies - Lin, Bo; Teo, Eng Wah; Yan, Tingting (Frontiers in Psychology, 2022)
The accurate measurement of university students’ motivation to participate in physical activity (PA) is a prerequisite to developing better physical fitness programs. However, motivation driven by government policies, i.e., physical education policies, are often excluded from many existing scales. The purpose of this study was to develop and evaluate a psychometric instrument based on self-determination theory that exclusively measures the motivation of Chinese university students to participate in PA. A total of 1,215 university students who regularly participated in PA at five universities in China constituted the final valid sample. Sample 1 (n = 311) was used to determine the underlying factor structure of the initial Chinese University Students’ Physical Activity Motivation Scale (CUSPAMS) through exploratory factor analysis (EFA). Sample 2 (n = 330) was used to test the model fit of the EFA-derived factor structure and data through confirmatory factor analysis (CFA) and to test the internal consistency of each factor and of the whole scale. Sample 3 (n = 574) was used to confirm the model stability and criterion validity. Finally, 177 individuals were randomly selected from Sample 3 to perform test–retest reliability. Preliminary evidence showed that the nine-factor CUSPAMS, consisting of 32 items, yielded good psychometric characteristics. The development of the CUSPAMS provides an opportunity to improve current theories and practices regarding the assessment of PA motivation. The CUSPAMS is recommended for examining factors that influence motives as well as the impact of motives on PA among Chinese university students.